Global signaling effects of a schizophrenia-associated missense mutation in neuregulin 1: an exploratory study using whole genome and novel kinome approaches - Marballi, Ketan K. (2014)
Aberrant neuregulin 1-ErbB4 signaling has been implicated in schizophrenia. We previously identified a novel schizophrenia-associated missense mutation (valine to leucine) in the NRG1 transmembrane domain. This variant inhibits formation of the NRG1 intracellular domain (ICD) and causes decreases in dendrite formation. To assess the global effects of this mutation, we used lymphoblastoid cell lines from unaffected heterozygous carriers (Val/Leu) and non-carriers (Val/Val). Transcriptome data showed 367 genes differentially expressed between the two groups (Val/Val N = 6, Val/Leu N = 5, T test, FDR (1 %), α = 0.05, -log10 p value >1.5). Ingenuity pathway (IPA) analyses showed inflammation and NRG1 signaling as the top pathways altered. Within NRG1 signaling, protein kinase C (PKC)-eta (PRKCH) and non-receptor tyrosine kinase (SRC) were down-regulated in heterozygous carriers. Novel kinome profiling (serine/threonine) was performed after stimulating cells (V/V N = 6, V/L N = 6) with ErbB4, to induce release of the NRG1 ICD, and revealed significant effects of treatment on the phosphorylation of 35 peptides. IPA showed neurite outgrowth (six peptides) as the top annotated function. Phosphorylation of these peptides was significantly decreased in ErbB4-treated Val/Val but not in Val/Leu cells. These results show that perturbing NRG1 ICD formation has major effects on cell signaling, including inflammatory and neurite formation pathways, and may contribute significantly to schizophrenia pathophysiology.